A computational chemist's guide to accurate thermochemistry for organic molecules. (15th February 2016) - Karton, Amir
Abstract : Composite ab initio methods are multistep theoretical procedures specifically designed to obtain highly accurate thermochemical and kinetic data with confident sub‐kcal mol −1 or sub‐kJ mol −1 accuracy. These procedures include all energetic terms that contribute to the molecular binding energies at these levels of accuracy (e.g., CCSD(T), post‐CCSD(T), core–valence, relativistic, spin‐orbit, Born–Oppenheimer, and zero‐point vibrational energy corrections). Basis‐set extrapolations (and other basis‐set acceleration techniques) are used for obtaining these terms at sufficiently high levels of accuracy. Major advances in computer hardware and theoretical methodologies over the past two decades have enabled the application of these procedures to medium‐sized organic systems (e.g., ranging from benzene and hexane to amino acids and DNA bases). With these advances, there has been a proliferation in the number of developed composite ab initio methods. We give an overview of the accuracy and applicability of the various types of composite ab initio methods that were developed in recent years. General recommendations to guide selection of the most suitable method for a given problem are presented, with a special emphasis on organic molecules. WIREs Comput Mol Sci 2016, 6:292–310. doi: 10.1002/wcms.1249 This article is categorized under: Electronic Structure Theory > Ab Initio Electronic Structure Methods Theoretical and Physical Chemistry > Thermochemistry Abstract :